(untitled) (Research, Society and Development, 2020)
The objective of the work was to carry out an integrative literature review on the microbiological control and hygienic-sanitary conditions of hamburger sandwiches. This is an exploratory review with a theoretical approach with a search for articles published between 2009 and 2020 that were related to the topic addressed, had a full text and were located in the PubMED, SciELO, VHL and Google Scholar databases. To survey the research, the descriptors in the Portuguese language were used: Microbiological analysis, Microbiological contamination and Hamburger; in English: Microbiological analysis, Microbiological contamination and Hamburger and in Spanish: Microbiological analysis, Microbiological contamination and Hamburguesa. The Boolean AND operator was used to connect the descriptors in the English language. 27 researches were found related to the theme and after thorough analysis respecting the inclusion criteria, 11 references remained that fit the study. Among the surveys, those published in national journals, followed by international ones, prevailed. The researched publications showed that hamburgers are widely manipulated and that the lack of hygiene during their processing and in the places where meals are prepared are the main risk factors for cross contamination of the product. There is a need to implement good production practices in the processing of artisanal hamburgers, and training for handlers to avoid microbiological contamination of the food. Based on the necessary studies, it is possible to conclude that there is a relationship between inadequate hygienic-sanitary conditions and unsatisfactory microbiological quality, impossible in the contamination of products.